Systems Pharmacology Study of the Anti-Liver Injury Mechanism of Citri Reticulatae Pericarpium - Wu, Jianxiong; Ye, Xietao; Yang, Songhong; Yu, Huan; Zhong, Lingyun; Gong, Qianfeng (Frontiers in Pharmacology, 2021)
The liver is the largest metabolic organ of the human body, and one direct cause of hepatocyte damage is lipid peroxidation on the plasma or cell membrane, which inactivates cells and can even induce carcinogenesis. Citri Reticulatae Pericarpium (CRP) is one of the most commonly used traditional Chinese medicines, and flavonoids such as hesperidin, nobiletin, and tangeretin are its main components. CRP has antibacterial, antioxidant, and antitumor effects that can reduce cholesterol, prevent atherosclerosis, and are effectively anti-liver injury (LI). Given that the specific components and mechanism of action of CRP against LI have not been clarified, we analyzed the components of CRP and their targets of action for the treatment of LI and the relationships between them using a systems pharmacology approach. Twenty-five active ingredients against LI were selected based on ultra-performance liquid chromatography-quadrupole/time-of-flight mass spectrometry and databases, and the drug targets and disease-related targets were predicted, resulting in 117 common targets, and then a Protein–Protein Interaction network was constructed. The results showed that there were 1719 Gene Ontology items in the treatment of LI, including 1525 Biological Process, 55 Cellular Component, and 139 Molecular Function. Next, 49 Kyoto Encyclopedia of Genes and Genomes pathways were found to be correlated with them. These findings suggest that CRP may play a role in counteracting LI mainly by affecting apoptotic, inflammatory, and energy metabolism modules. In vitro cell experiments suggest that the mechanism by which CRP counteracts LI may be that hesperidin and naringenin act on CASP3, BAX and BCL2 to affect the apoptosis pathway, which in turn attenuates liver fibrosis. In addition, naringenin significantly inhibited the phosphorylation of AKT1, which in turn mediated phosphoinositide 3-kinase-Akt signaling pathways against LI. This study provides a reference for systematically exploring the mechanism of CRP anti-LI action and is also an expansion of the application of systems pharmacology in the study of traditional Chinese medicine.